Protective Effects of Proanthocyanidin on Cerulein-induced Acute Pancreatic Inflammation in Rats - (:unkn) unknown (My University, 2009)
BACKGROUND: The aim of this study was to assess the possible protective effect of proanthocyanidin against cerulein-induced acute pancreatic inflammation (AP) and oxidative injury. METHODS: Sprague-Dawley rats were pretreated with proanthocyanidine (100 mg/kg, orally) or saline 15 min before cerulein was given by 20 µg/kg subcutaneously at 1-h intervals within 4 hours. Six hours after cerulein or saline injections, the animals were killed by decapitation. Blood samples were collected to analyze amylase, lipase, and proinflammatory cytokines (TNF-α and IL-1b). Pancreas tissues were taken for the determination of tissue glutathione (GSH) and malondialdehyde (MDA) levels, Na+, K+-ATPase and myeloperoxidase (MPO) activities. Formation of reactive oxygen species in pancreatic tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probes, while the extent of tissue injury was analyzed microscopically. RESULTS: Acute pancreatitis caused a significant decrease in tissue GSH level and Na+, K+-ATPase activity, which was accompanied with significant increases in the pancreatic MDA, luminol and lucigenin chemiluminescences (CL) levels and MPO activity. Similarly TNF-α and IL-1β levels were elevated in the pancreatic group as compared to control group. On the other hand, proanthocyanidin treatment reversed all these biochemical indices, as well as histopathological alterations that were induced by cerulein. CONCLUSIONS: Proanthocyanidine can ameliorate pancreatic injury induced by cerulein in rats, this result suggests that proanthocyanidin may have utility in treating acute pancreatititis.
Keywords: Glutathione; Cytokines; Pancreatitis; Myeloperoxidase activity; Proanthocyanidine; Tumor Necrosis Factor alpha